2016
DOI: 10.1097/md.0000000000004952
|View full text |Cite
|
Sign up to set email alerts
|

Uncommon liver tumors

Abstract: Background:Beside hepatocellular carcinoma, metastasis, and cholangiocarcinoma, the imaging findings of other relatively uncommon hepatic lesions are less discussed in the literature. Imaging diagnosis of these lesions is a daily challenge. In this article, we review the imaging characteristics of these neoplasms.Methods:From January 2003 to December 2014, 4746 patients underwent liver biopsy or hepatic surgical resection in our hospital. We reviewed the pathological database retrospectively. Imaging of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 70 publications
0
21
0
Order By: Relevance
“…These palliative treatments were associated with various outcomes in previous studies [11]. Most studies showed that chemotherapy and radiation therapy had no significant effect on survival [11, 20, 28]. Liver transplant for patients with PHA should not be recommended to patients with a high tumor recurrence rate and a median survival time of less than seven months after liver transplant [20].…”
Section: Discussionmentioning
confidence: 99%
“…These palliative treatments were associated with various outcomes in previous studies [11]. Most studies showed that chemotherapy and radiation therapy had no significant effect on survival [11, 20, 28]. Liver transplant for patients with PHA should not be recommended to patients with a high tumor recurrence rate and a median survival time of less than seven months after liver transplant [20].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the radiologic findings of IPT-like FDC tumors of the liver have rarely been described. We only found two reports that briefly mention the imaging features of IPT-like FDC tumors of the liver (see Wu et al[14]), where the tumor appeared as a well-defined, heterogeneous arterial-enhanced mass without significant portovenous washout. However, this study did not provide the delay phase images; in another case report study[3], they only showed portal phase images without a summary of imaging appearances.…”
Section: Discussionmentioning
confidence: 99%
“…On ultrasound, PHL most often appears as an homogeneous hypoechoic lesion with well-defined margins [50]. On contrast enhanced ultrasound, there is washout on late phase [51]. CT demonstrates hypoenhancement in comparison to normal liver parenchyma during both arterial and delayed phases with occasional rim enhancement [48,52].…”
Section: Primary Hepatic Lymphomamentioning
confidence: 99%